Methodology Development and Initial Results of CFD Simulations of Methane Distribution in the Working of a Longwall Ventilated in a Short “Y” Manner - Janoszek, Tomasz; Krawczyk, Jerzy (Archives of Mining Sciences, 2022)
The mining in seams with a high methane content by means of a longwall system, under conditions of high extraction concentration, results in exceeding methane concentrations allowed by the regulations at workings of the longwall environment, with the effect of mining machines’ standstill periods. The paper is a part of a study supporting the development of a system for shearing cutting speed control at the longwall, which should substantially reduce the production standstills due to exceeded limits and switching off the supply of electric equipment. Such a control system may be appropriate for longwalls ventilated using “Y” and “short Y” methods. Efficient Computer simulations of the 3D airflow and methane propagation may assist the design and initial evaluation of the control system performance. First chapters present studies that are necessary for a proper formulation of the properties of the longwall model. Synthetic analysis of production during the period of longwall operation allowed one to choose the input assumptions to carry out ventilation-methane computations in a CFD numerical model of longwall Z-11. This study is followed by a description of the model that is used for a case study, considering three variants of the shearer position. Finally, initial simulation results and directions of further studies are discussed.
Keywords: modelling; methane; CFD; underground mining; natural hazards; shearer